The Effect of Odd One Out Game on Primary Students’ Vocabulary Retention - Naibaho, Debora Natalia; Fauzan, Akhmad; Fikri, Muhammad Subhan; Carolina, Reyssa Aurora; Nastiti, Diana Febri Wuri (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
This study examines the effect of using the Odd One Out game to improve students’ knowledge of clothing-related English vocabulary. The research includes introducing the Odd One Out game to students, explaining its concepts, planning and designing lessons using this game, evaluating and measuring learning outcomes. The study was conducted at SDN 6 Menteng, Central Kalimantan, involving 26 fifth-grade students from class 5B. This game incorporates in-depth material exploration, development of learning activities, and group discussions in the classroom. Implementing the Odd One Out game has demonstrated that students in the school significantly improved their knowledge of clothing-related English vocabulary. The learning process also fostered a competitive and engaging classroom environment. The implementation of the learning process through the Odd One Out game was conducted successfully and efficiently. Game-based learning methods can serve as an effective solution to address the low interest of elementary school students in learning English vocabulary.